(untitled) (Journal of Global Humanities and Social Sciences, 2024)
Mechanical patent specifications are carriers of technological innovation, and their translation not only needs to accurately convey the technical information of the source language, but also conforms to the expression habits of the target language, so as to ensure that readers in cross-cultural and cross-linguistic backgrounds can understand and apply the relevant technologies. The purpose of this paper is to explore the translation strategy of mechanical patent specifications under the guidance of the theory of functional equivalence, so as to make the translated text functionally the same as the source language through the techniques of lexical, syntactic, chapter and style equivalence. To this end, this paper adopts the method of literature analysis, through combing the relevant theories and research results, and analysing the translation strategies in practice with actual cases. Through such research, this paper strives to provide effective guidance for the translation of mechanical patent specifications within the framework of the functional equivalence theory, and to promote the accurate communication and smooth application of patent information in international technical exchanges.